Nordic walking jako współczesna forma aktywności seniorów =Nordic walking as a contemporary activity form of seniors - Molesztak, Aldona (Journal of Education, Health and Sport, 2016)
Molesztak Aldona. Nordic walking jako współczesna forma aktywności seniorów = Nordic walking as a contemporary activity form of seniors. Journal of Education, Health and Sport. 2016;6(12):365-375. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.202289 http://ojs.ukw.edu.pl/index.php/johs/article/view/4069 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 14.12.2016. Nordic walking jako współczesna forma aktywności seniorów Nordic walking as a contemporary activity form of seniors Aldona Molesztak Wydział Pedagogiki i Psychologii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: aktywność ruchowa, Nordic Walking, seniorzy Key words: physical activity, Nordic Walking, seniors Streszczenie W każdym człowieku zachodzi stopniowy proces starzenia się. Jednak tempo tego procesu jest zindywidualizowane. Proces ten może zostać spowolniony w sytuacji wystąpienia korzystnych czynników, do których należy aktywność ruchowa. Podejmowanie aktywności ruchowej wpływa na układ krążenia, oddechowy, ruchu, nerwowy, odpornościowy, zmniejsza problemy związane z ciśnieniem tętniczym, obniża ryzyko wystąpienia demencji, ogranicza ryzyko upadku, zwiększa energię podczas chodzenia i poprawia postawę jednostki. Wyniki badań wskazują, że doskonałą formą aktywności dla seniorów jest nordic walking ze względu na możliwość indywidualnego dostosowania do możliwości jednostki, terenu marszu, brak ograniczeń czasowych i nakładów finansowych. Abstract Every human being experiences the gradual process of aging, however, differences can be observed as to its pace in individual cases. The process can be slowed down owing to such beneficial factors as physical activity. Physical exercise has a positive influence on the circulatory, respiratory, locomotor, nervous and immune systems, reduces health problems related to blood pressure and the danger of dementia, limits dangers of falling down at the same time increasing the body energy during walks and improving the body posture. Results of recent studies have pointed to Nordic walking as a form of physical exercise perfect for seniors due to the fact that it is easy to adjust it to individual abilities, the terrain, time scope and financial means.